Pemasaran Ideologi Negara melalui Kebijakan Pendidikan: Strategi Komunikasi Politik Implementasi Pendidikan Pancasila di Bawah Kementerian Agama: Political Communication Strategies in Pancasila Education: Promoting State Ideology within the Ministry of Religious Affairs' Educational Framework - Suryanto Kurniawan Putra; Maersk Ramadani Gumay (Bhinneka Tunggal Ika: Pancasila Jurnal Internasional Berbahasa Indonesia, 2026)
This article examines the implementation of Pancasila Education and the Main Textbook (BTU) of Pancasila Education in educational institutions under the coordination of the Ministry of Religious Affairs as a form of non-electoral state political communication. Drawing on political marketing and public policy communication perspectives, the study conceptualizes the state as an actor that markets Pancasila ideology through formal educational institutions. Using a qualitative approach, data were collected through in-depth interviews, focus group discussions, questionnaires, and policy document analysis. The findings indicate that despite strong regulatory legitimacy, Pancasila Education is predominantly implemented in an administrative manner. Fragmented teacher understanding, weak management of message distribution channels, and the limited role of teachers as intermediary actors reduce the state’s ideological persuasive capacity. The article argues that the effectiveness of Pancasila Education depends on persuasive, consistent, and audience-oriented ideological communication strategies rather than regulatory strength alone.